2017
DOI: 10.1136/bmjqs-2017-006761
|View full text |Cite
|
Sign up to set email alerts
|

Improving admission medication reconciliation with pharmacists or pharmacy technicians in the emergency department: a randomised controlled trial

Abstract: NCT02026453.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 21 publications
0
73
0
1
Order By: Relevance
“…Many studies have described the benefits of using pharmacy support personnel to facilitate TOC, including reduced readmissions, resolved medication‐related problems, and improved patient satisfaction and understanding of medications . Specifically, pharmacy support personnel can obtain complete medication histories and perform medication reconciliation, update medication lists in the health record, and document TOC activities . Because of the nature of these tasks, pharmacist extenders should display professionalism and possess strong communication skills, attention to detail, and self‐motivation.…”
Section: Role Of Pharmacy Support Personnel In Tocmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have described the benefits of using pharmacy support personnel to facilitate TOC, including reduced readmissions, resolved medication‐related problems, and improved patient satisfaction and understanding of medications . Specifically, pharmacy support personnel can obtain complete medication histories and perform medication reconciliation, update medication lists in the health record, and document TOC activities . Because of the nature of these tasks, pharmacist extenders should display professionalism and possess strong communication skills, attention to detail, and self‐motivation.…”
Section: Role Of Pharmacy Support Personnel In Tocmentioning
confidence: 99%
“…When paired with discharge medication reconciliation, bedside medication delivery can improve medication adherence and reduce medication errors and readmissions. 23 27,28 Because of the nature of these tasks, pharmacist extenders should display professionalism and possess strong communication skills, attention to detail, and self-motivation. Furthermore, experience in pharmacy, managed care, hospital, or diverse settings can better prepare pharmacy support personnel to identify common sources of medication errors.…”
Section: Clinical Pharmacists' Roles In Tocmentioning
confidence: 99%
“…California found that pharmacists and pharmacy technicians were equally effective in reducing admission medication history errors and related admission medication orders. 3 Dr. Rita Shane, CSMC Chief Pharmacy Officer, highlighted her research in drafting and advocating for Senate Bill 1254 in California, which requires pharmacists, interns, or technicians to obtain accurate medication profiles/lists for high-risk patients admitted to hospitals with more than 100 beds. 4 The bill was signed into law on September 22, 2018 and marks the first mandate in the state for pharmacy to engage directly with patients in hospitals.…”
Section: For Example a Study From Cedars-sinai Medical Center (Csmc) Inmentioning
confidence: 99%
“…At the same time, this should not be a reason to wait for further guidance before challenging appropriately trained pharmacy technicians with clinical duties to advance clinical programs and policy efforts. For example, a study from Cedars‐Sinai Medical Center (CSMC) in California found that pharmacists and pharmacy technicians were equally effective in reducing admission medication history errors and related admission medication orders . Dr. Rita Shane, CSMC Chief Pharmacy Officer, highlighted her research in drafting and advocating for Senate Bill 1254 in California, which requires pharmacists, interns, or technicians to obtain accurate medication profiles/lists for high‐risk patients admitted to hospitals with more than 100 beds .…”
mentioning
confidence: 99%
“…In recent years, there has been some growth in the body of literature on extended/advance roles and although these are generally limited to small local studies, they do provide insight into pharmacy technician role development [3][4][5][6][7]. The literature also highlights the positive contribution that pharmacy technicians, with specific training, can make to pharmacy services and patient care, with the general theme that the extended roles release pharmacists for more patient-facing clinical activity and further developing their clinical skills and knowledge to train as nonmedical prescribers.…”
Section: Introductionmentioning
confidence: 99%